Marketing Strategy of KLM™ - Chairunisa, Rahmah; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2012)
KLM is one of PT. XYZ product that managed by Health Care Business unit. KLM is a transparent intravenous dressing that aims to reduce the number of phlebitis and IADP (Primary blood stream infections). Among the intravenous dressing, KLM only can seize 29% of market share in Indonesia. And in 2011, the sales of KLM were decline for more than 50% from sales in 2010. This condition happened in DKI Jakarta and Bandar Lampung. While on the other regions, the number of sales is too volatile. Since PT. XYZ has already implemented marketing strategy for KLM, the exisiting marketing strategy of KLM has to be evaluated to increase the market share and number of sales.The conceptual framework which is used is coming from the external factor of PT. XYZ and internal factor as well. The external factor is using Porter Five Forces analysis, Situation analysis (5C), and Perceptual map. And the internal factor is using marketing mix, product life cycle, and customer analysis. The samples are taken from hospitals in Jakarta. The sampling structure is intended to review the actual wants of KLM’s customers.The root cause analysis has resulted in three areas of improvement: (1) KLM has ineffective marketing communication, (2) the relationship with distributor that not well maintained and cause the distributor not focus in selling KLM, and (3) the relationship with the customer that not maintained properly.The recommendation includes the improvement in more effective marketing strategy, relationship with the distributor and customer as well. The activities targets are the nurse division, especially the head of nurses and infection control nurse, the hospital management, and PPNI as the influencer. The strategies including product introduction, product trial, brochures, seminar and workshop, and seminar sponsorship. The estimated budget for the new marketing strategy and relationship management is Rp 332,890,000.- for one year. Keywords: Marketing strategy, Relationship management, KLM, Transparent intravenous dressing